1997
DOI: 10.1007/s000110050183
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction enhances the portal venous histamine level in dogs

Abstract: Histamine is released into the gastrointestinal tract during acute myocardial ischemia and reperfusion, but the release of the vasoactive drug has no effect on systemic hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Our finding of an elevation in serum histamine after AMI is consistent with previous studies 8 9 10 12 . The degranulation of mast cells 16 17 18 and activation of sympathetic nerves 30 were reported to be responsible for the immediate elevation of histamine after the onset of AMI, but mast cells are able to provide only a temporary pulse of histamine release.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of an elevation in serum histamine after AMI is consistent with previous studies 8 9 10 12 . The degranulation of mast cells 16 17 18 and activation of sympathetic nerves 30 were reported to be responsible for the immediate elevation of histamine after the onset of AMI, but mast cells are able to provide only a temporary pulse of histamine release.…”
Section: Discussionsupporting
confidence: 93%
“…Histamine is a biogenic amine which is widely distributed and has many functions 4 5 6 7 . Several studies have found that the levels of histamine in the serum and myocardium increased significantly in acute myocardial infarction (AMI) 8 9 10 11 12 . Mast cells have been considered to be the primary cellular source of histamine.…”
mentioning
confidence: 99%
“…All dogs had baseline histamine concentrations that were within the range reported in the literature. 4,21 The assay used for plasma histamine concentration in our study is a verified method. 22 It is possible that IV administration of hydromorphone could induce histamine release from mast cells.…”
Section: Discussionmentioning
confidence: 87%
“…Histamine is a biogenic amine, which is widely distributed and possesses many biological functions 24 27 . There are growing researches including ours reporting that histamine in the serum and myocardium increased significantly after AMI 26 , 28 31 . Recent work demonstrated that histamine deficiency exacerbates AMI-induced cardiomyocyte apoptosis, indicating that endogenous histamine might exhibit a protective effect during MI 30 .…”
Section: Introductionmentioning
confidence: 94%